Marktdesign für die Gasmangellage; Market design for a gas shortage - Axel Ockenfels (Wirtschaftsdienst, 2022)
Bisher ist unklar, wer wie viel Gas zu welchem Preis in einer Mangellage in Deutschland bekommt, wenn der Regulierer rationieren muss. Dies droht die Anreize in und im Vorfeld einer Mangellage zu verwässern. In diesem Beitrag wird die potenziell hilfreiche Rolle eines Zertifikatsmarktes für die Allokation und Bepreisung in der Mangellage in den Blick genommen. – – So far, it is unclear who will get how much gas at what price in a gas shortage situation in Germany when the regulator has to ration. This threatens to dilute incentives in and in advance of a shortage. This paper looks at the potentially helpful role of a market for gas usage certificates for allocation and pricing in a shortage situation.
Keywords: D47; H12; Q41; 330